The research frontier of cesarean section recovery: A bibliometric analysis - Zhao, Lizheng; Wei, Hong (Frontiers in Medicine, 2022)
Background: Cesarean section (CS) has become an effective means to solve dystocia and some obstetric complications, and to save the lives of women and perinatal women. Disparities in quality obstetric care and rehabilitation in CS result from differences in health care systems across regions, and more scientific and reasonable rehabilitation programmes and management measures will benefit more parturient and newborns worldwide who have to take CS. In this study, we performed a bibliometric analysis to collect a graphical representation of the CS recovery. Methods: A total of 995 documents of CS recovery were retrieved from the Web of Science Core Collection (WOSCC) on December 31, 2021, and then VOSviewer 1.6.18 was used for visual analysis. Results: Over the last 20 years, the researches of CS recovery has gradually increased and it will continue to grow in the next period. Anesthesia and Analgesia is the most popular journal in CS recovery. Most of the representative achievements are concentrated in the relevant institutions of European and American countries, Brendan Carvalho and Ian J Wrench are among the outstanding scholars in this field, but the overall outcome is limited by limited regional work and lack of broad cooperation and representation. “CS”, “surgery”, “management”, “recovery”, “enhanced recovery”, and “risk factors” are high frequency keywords, and there is a close relationship between “management” and “enhanced recovery” around the CS and they also become one of the key factors to regulate the condition of patients. Conclusion: This work firstly analyzed the research condition of CS recovery by a bibliometric analysis. According to the practice guideline, it produces some outstanding representative productions, which involves enhanced recovery after surgery (ERAS) and will continue to be the focus of researchers. More substantive research articles and large-scale clinical studies may greatly enhance the scientific value, and it is necessary to strengthen the ERAS guideline and cooperation between researchers, generate broader consensus and results, and ultimately provide help for CS recovery.